Delayed Infection of a Lymphocele following RARP in a Patient with Nonspecific Symptoms. (15th March 2017) - Taniguchi, Tomoki; Takahashi, Yoshito; Taniguchi, Mitsuhiro; Yamada, Toru; Ishida, Kenichiro
Abstract : Pelvic lymphoceles are an infrequent complication after pelvic surgery and develop shortly after the surgery in most cases. We experienced a case of delayed infection of a lymphocele 6 months after robot-assisted radical prostatectomy (RARP) and pelvic lymphadenectomy. In this case, antimicrobial chemotherapy and percutaneous drainage were effective, and there was no recurrence of the disease. Most urologists do not recognize that infected lymphoceles can develop a long time after surgery; thus, infected lymphoceles should be kept in mind in patients with nonspecific infectious symptoms, regardless of the length of time after surgery.